Zinc deficiency as a possible risk factor for increased susceptibility and severe progression of Corona Virus Disease 19. Issue 2 (28th January 2022) - Wessels, Inga; Rolles, Benjamin; Slusarenko, Alan J.; Rink, Lothar
Abstract: The importance of Zn for human health becomes obvious during Zn deficiency. Even mild insufficiencies of Zn cause alterations in haematopoiesis and immune functions, resulting in a proinflammatory phenotype and a disturbed redox metabolism. Although immune system malfunction has the most obvious effect, the functions of several tissue cell types are disturbed if Zn supply is limiting. Adhesion molecules and tight junction proteins decrease, while cell death increases, generating barrier dysfunction and possibly organ failure. Taken together, Zn deficiency both weakens the resistance of the human body towards pathogens and at the same time increases the danger of an overactive immune response that may cause tissue damage. The case numbers of Corona Virus Disease 19 (COVID-19) are still increasing, which is causing enormous problems for health systems and economies. There is an urgent need to reduce both the number of severe cases and the resulting deaths. While therapeutic options are still under investigation, and first vaccines have been approved, cost-effective ways to reduce the likelihood of or even prevent infection, and the transition from mild symptoms to more serious detrimental disease, are highly desirable. Nutritional supplementation might be an effective option to achieve these aims. In this review, we discuss known Zn deficiency effects in the context of an infection with Severe Acute Respiratory Syndrome-Coronavirus-2 and its currently known pathogenic mechanisms and elaborate on how severe pre-existing Zn deficiency may pre-dispose patients to a severe progression of COVID-19. First published clinical data on the association of Zn homoeostasis with COVID-19 and registered studies in progress are listed.